The Role of Microteaching in Enhancing Teaching Skills for Prospective Teachers in the Professional Teacher Education Program at UMS Rappang - M Nurzin Kasau; Aswadi Aswadi; Jumiati Jumiati; Usman M; Muhammad Hanafi; Sam Hermansyah; Ruswati Ruswati; Sanati Sanati (Edumaspul: Jurnal Pendidikan, 2024)
Microteaching plays a significant role in enhancing the teaching skills of prospective teachers, particularly in the Professional Teacher Education Program (PPG) at UMS Rappang. This method offers a structured and systematic approach to prepare future educators for real classroom settings by simulating teaching experiences in a controlled environment. Through microteaching, participants practice specific teaching skills such as lesson planning, classroom management, and effective communication. They also receive direct feedback from peers and mentors, allowing them to reflect and improve continuously. The implementation of microteaching at UMS Rappang has shown to boost pedagogical competence, confidence, and readiness among prospective teachers, ultimately contributing to the improvement of educational quality.